1975
DOI: 10.1071/pp9750051
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Immature Pea Cotyledons in Culture

Abstract: Detached immature pea (Pisum sativum) cotyledons grow for several days in liquid medium and synthesize considerable quantities of chlorophyll, starch, DNA, RNA and protein (including the storage proteins vicilin and legumin). Seeds developing in detached pods also synthesize both major storage proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Several observations (3,8,10,15,24) indicate that arginine, accumulating in large amounts in developing cotyledons, is synthesized in situ. Gln, the preferred N donor for CAP in vitro, is available as N donor in situ, inasmuch as the endospermic fluid, the fruit phloem sap, and cotyledons at an early developmental stage contain relatively high amounts of Gln (3,10,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations (3,8,10,15,24) indicate that arginine, accumulating in large amounts in developing cotyledons, is synthesized in situ. Gln, the preferred N donor for CAP in vitro, is available as N donor in situ, inasmuch as the endospermic fluid, the fruit phloem sap, and cotyledons at an early developmental stage contain relatively high amounts of Gln (3,10,24).…”
Section: Discussionmentioning
confidence: 99%
“…The assay mixture, in a total volume of 1.20 ml and a final pH of 8.1, contained 50 ,umol L-Gln, 10 ,umol ATP, 7.5 ,tmol Na214CO3 (0.1 Ci/mol), 15 ,Imol MgCl2, 5 ,umol of L-Orn, and 60 ,umol of Tricine-KOH buffer. The reaction was initiated by the addition of 0.5 ml extract and allowed to proceed for 15 min at 30°C.…”
mentioning
confidence: 99%
“…Cotyledons were cultured as described by Weber et al (1995) in a medium, according to Millerd et al (1975), containing 70 mM L-glutamine, 0.1 mg/L benzyladenine, and 0.02 mg/L naphthaleneacetic acid. Sugars were supplemented as indicated.…”
Section: In Vitro Culture Of Cotyledonsmentioning
confidence: 99%
“…A transfer of reserves of C or N was assumed from observation of losses by pods and gains by seeds. Pfenninger (23) that seeds of Vicia faba continued their development after removal from the plant, and several studies have reported continuing seed growth in detached pods of Pisum sativum (3,14,18,26) and Glycine max (19) cultured in aseptic conditions. In the latter, the potential role of pod tissues in supporting seed growth was not examined directly since contributing nutrition from the culture medium was involved to an unknown extent.…”
mentioning
confidence: 99%